Antioxidant Activity Tests of Extract of Principle Crafts (Phaleria macrocarpa) - Tri Putri; Anang W. M. Diah; Afadil Afadil (Jurnal Akademika Kimia, 2019)
Phaleria macrocarpa contains secondary metabolite compounds such as alkaloids, terpenoids, saponins, polyphenols, tannins, sterols, and coumarins. Those metabolites are antioxidants and can be efficacious in the healing of various degenerative diseases such as cervical cancer and diabetes. This plant is widely grown in Tindaki Village, Parigi Mautong, Central Sulawesi. The aim of this study was to determine the antioxidant power of those phaleria macrocarpa fruit extract. This study was conducted by using maceration extraction technique with ethanol as solvent, and compound 2,2-difenil-1-picrilhidrazil (DPPH) as source of free radical, and vitamin C as the positive control. The UV-Vis spectrophotometer was used to measure the absorbance of the extract. Various concentrations of the extract used were 5 ppm, 15 ppm, 25 ppm, and 35 ppm. The results showed that the IC50 value of the fruit extract was 28.242 ppm, while the IC50 value of vitamin C was 19.302 ppm. These IC50 values show that vitamin C was a stronger antioxidant activity than the fruit extract, but the fruit extract was still as a very strong natural antioxidant category.